Non‐BCMA targeted CAR‐T cell therapies for multiple myeloma. Issue 2 (20th September 2021) - Wang, Xiangmin; Pan, Bin; Huang, He; Xu, Kailin
Abstract: Despite the emergence of new strategies in recent years, multiple myeloma (MM) is still an incurable disease with poor outcome. As a new treatment, chimeric antigen receptor (CAR‐) T cell therapy brought exciting news to patients with relapsed or refractory MM. B‐cell maturation antigen (BCMA) is ubiquitously expressed on the surface of myeloma cells and is considered an "ideal" target of CAR‐T cell. BCMA‐targeted CAR‐T cell therapies achieved remarkable efficacy in relapsed or refractory MM patients in several clinical trials. However, some patients had no response or relapsed after BCMA targeted CAR‐T cell therapy. Myeloma cells also express other surface markers which might be used as targets for CAR‐T cell therapy. Encouragingly, CAR‐T cells targeting these non‐BCMA markers are being tested in clinical trials or under preclinical investigation, already showing some promising results. In this review, we summarized and provided an update of these advances.